Islamic Leadership and Employee Loyalty: Empirical Evidence from PT Multi Servisindo Sarana - R Muhammad Kevin Satrya Aji Bramantyo; Ahmad Maulidizen (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study investigates the influence of Islamic leadership on employee loyalty at PT Multi Servisindo Sarana, an Indonesian security service company operating in a highly competitive outsourcing industry where employee retention has become a critical organizational challenge. Islamic leadership is conceptualized through four prophetic leadership dimensions: Shiddiq (truthfulness), Amanah (trustworthiness), Tabligh (effective communication), and Fathonah (wisdom and competence). A quantitative research design was employed using a structured questionnaire distributed to employees selected through probability sampling with a simple random sampling technique. From a population of 1,056 employees, a sample size of 91 was determined using the Slovin formula. Data were analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis with SPSS. The findings reveal that Amanah has a positive and statistically significant effect on employee loyalty, whereas Shiddiq, Tabligh, and Fathonah do not exhibit significant partial effects. However, the four dimensions of Islamic leadership jointly have a significant influence on employee loyalty (F = 31.391; p < 0.001), explaining 59.4% of the variance in employee loyalty (R² = 0.594). These findings suggest that trustworthiness represents the most influential leadership attribute in strengthening employee loyalty within the security services industry. The study recommends that organizations reinforce leadership practices grounded in Islamic values, particularly Amanah, to foster employee commitment, organizational stability, and long-term organizational performance.